Efektifitas Sabun Cair Ekstrak Kulit Nanas Sebagai Pembersih Basis Gigi Tiruan Resin Akrilik Heat Cured Terhadap Pertumbuhan Candida Albicans - Tiffany Augusta Posuma; Meinar Nur Ashrin; Dwi Andriani (Denta Journal Kedokteran Gigi, 2016)
Background: Candida albicans acts as a trigger to denture stomatitis. Prevention of denture stomatitis can be done by cleaning dentures with mechanic and chemical methods. Bromelin enzymes from pineapple can be use as a chemical substance to purify dentures for its ability to prevent the growth of Candida albicans with its proteolytic activity. Objectives: to determine the influence of soap from pineapple peel extract as acrylic resin heat cured denture cleanser in Candida albicans impure. Materials and Methods: The experiment is post test only group design. The subject is divided into 6 groups. Control group (aquadest), Positive control group (soap with lime extract brand X), and four treatment groups (soap from pineapple peel extract with 0%, 3,5%, 7%, and 14% concentration). Each group is brushed with an electric tooth brush for 5’. Then each sample is inserted into Saboraud Dextrose Broth and 0,1 ml is taken and is vortexed for 30’ then is incubated in Saboraud Dextrose Agar for 24 hours. The colony is counted with the colony counter in CFU/ml. The data will be tested with One Way ANOVA and continued with LSD test. Result: The mean of Candida albicans colony in K-, P1, P2, P3, P4, K+ is 44.00; 32.25; 2.25; 6.00; 11.50; 19.00. There is a difference between the control groups and all the treatment groups (p<0,05). Conclusions: Soap from pineapple peel extract with the concentration 3,5% is the most effective soap as an acrylic resin heat cured denture cleanser to influence the growth of Candida albicans